OPTIMIZING COMMUNICATION ETHICS IN THE DIGITAL AGE - Apdillah, Dicky; Salam, Agus; Tania, Ira; Lubis, Lili Kahirina Azhari (Transpublika Publisher, 2022)
The current Covid-19 pandemic has an impact on life today. One of them is the development of digital media which is changing very rapidly, all activities of people's lives that are transformed into all digital, of course, also have an impact on the style of communication between humans. This study aims to explain the ethics of communicating in today's digital era. One of them is the existence of social media. Due to the ease of using social media on digital media, users are often negligent in using communication etiquette. This research uses qualitative and descriptive research methods. From the results of the study, information was obtained that ethics and politeness norms are very necessary in communicating, especially in digital media. Communication ethics can be explored through a good understanding of grammar, early education about manners, learning to understand and limiting curiosity about the privacy of others.